Implementasi Sistem Informasi Akademik Menggunakan Aplikasi Jibas pada SMA Negeri 9 Padang - Ricky Akbar; Tuti Rahmawati; Amrullah . (Jurnal Nasional Teknologi dan Sistem Informasi, 2015)
SMA Negeri 9 Padang is one of the institutions engaged in the field of education, which requires the design of software to manage and run all school activities, one of which is the Academic Information System (SIA). SIA currently in SMA 9 Padang yet well integrated, so it still has many shortcomings in meeting the needs of the school or institution, in particular to deal with academic problems. Therefore, it needs to be implemented Academic Information System that can overcome the various shortcomings earlier. Implementation of this application starts with a preliminary study. Activities, the introduction of the school as a whole with interviews and observations, identify business processes academically at school is running and then make the proposed system as terkomputerisasinya, which is described by using the tools of Business Process Model Notation (BPMN), as well as the depiction of a working model of the system to be applied using use case diagram. The next stage is to study the literature of various books and journals to find the theoretical basis and related research. Then selecting software for SIA School, after the configuration and customization of the software modules, and the latter carry out the implementation and testing. These results indicate that the software SIA Schools that have been selected and applied that JIBAS applications, which can solve the problems on SMA Negeri 9 Padang